THE INFLUENCE OF BUSINESS ENVIRONMENT AND ORGANIZATIONAL CULTURE ON MANAGEMENT ACCOUNTING INFORMATION SYSTEM - Antonio, Gregorius Rudy; Safitri, Eni (jfpublisher, 2023)
Management Accounting Information System (MAIS) is an application used to connect, control, evaluate, and monitor employees in doing their work based on the standard and reach the work performance’s target. MAIS is a tool to identify, measure, collect, process, and interpret a company's information. It is also used as a medium to spread information and help the manager in the decision-making process. This study aims to know the effect of the business environment and organizational culture in hotels in Surabaya on the management accounting information system. Also, to analyse the moderation influence of gender, age, and job period in the business environment and organizational culture. The research results showed a positive influence between the business environment and organizational culture on MAIS and no influence on gender, age, and job period. The application of MAIS will be more effective if the environment and corporate culture are enhanced.